Unveiling Indonesia's Precautionary Principle for Trust in Digital Transactions: Mengungkap Prinsip Kehati-hatian Indonesia untuk Kepercayaan dalam Transaksi Digital - Santosa, Shilla Hasmara; Purwaningsih, Sri Budi (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: This research explores the compliance of the Sejuta Cita platform with Indonesia's Electronic Information and Transactions Law (ITE Law), specifically focusing on Article 28, which addresses misleading information in electronic transactions. The general background underscores the growing importance of digital platforms in event management, necessitating stringent adherence to legal standards. The specific background highlights the critical role of user verification processes in ensuring accurate information and responsible user behavior. Despite the increasing reliance on these platforms, a knowledge gap remains regarding the effective implementation of the precautionary principle within their operational frameworks. The primary aim of this study is to assess whether Sejuta Cita effectively incorporates the precautionary principle into its user verification processes, employing a normative juridical method with a statute approach that analyzes key legal frameworks, including Law No. 19 of 2016 and Law No. 11 of 2008. The results reveal that the platform’s terms of use mandate compliance with ethical norms and legal regulations, thereby emphasizing responsible decision-making during event registrations. The findings also indicate potential violations related to event content, yet confirm that Sejuta Cita's terms require event creators to adhere to applicable regulations. The novelty of this study lies in its detailed examination of the platform's user verification policies and their alignment with the ITE Law. The implications suggest that adherence to the precautionary principle enhances user trust and mitigates legal risks, contributing to the establishment of safer electronic transaction environments in Indonesia. Highlights: Compliance Assessment: Evaluates adherence to ITE Law on misleading information. User Verification: Analyzes precautionary principle implementation in user processes. Legal Framework: Assesses electronic agreements' implications for event organizers. Keywords: Sejuta Cita, ITE Law, user verification, precautionary principle, electronic transactions